Hizbullah a mission to nowhere - Khashan, Hilal, 1951- (Lexington Books, 2019)
This book examines the rise of Hizbullah and the marginalization and repression of Shi'ites that made them susceptible to exploitation by their sectarian leaders. It also explores how Hizbullah's abiding commitment to Iran's foreign adventures injured Lebanese Shi'ites and jeopardized their status beyond the boundaries of home.